PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP MOTIVASI KERJA KARYAWAN DI DIVISI BODY & RANGKA CV. LAKSANA - Muhammad Yusuf Amrulah; Agus Hermani DS (Universitas Diponegoro, 2018)
CV. Laksana as an autobody manufacture have some employees that have low level work motivation such as the employees cant finish production target on time, the employees doesnt have encouragement to start work early, the employees doesnt have encouragement to work every day, and the employees doesnt have encouragement to work by self-supporting. It is considered that the cause of these phenomena is the lack of employees’ work competency is still in low level and compensation achieved from the company are not good. This research is conducted to acknowledge the effect of competency and compensation towards the work motivation of CV. Laksana’s employees. The type of this research is assosiative research. The sample used in this research is 67 respondents who are employees from body and frame section in CV Laksana. The data are collected by questionnaire using Likert scale. The analyzing methods used in this research are validity and reliability test, coefficient correlation (R), regression test, determination coefficient (R 2 ), t and F signification test using SPSS 25.0 application. The result of this research shows that by partial competency and compensation variables have influenced work motivation positively and significantly with regression coefficient value in competency variable (0,543) and compensation (0,158) and value in t competency variable test (4,521) and t compensation variable test (1,746). And by simultaneous competency and compensations variables have influenced work motivation positively and significantly with regression coeficient value in competency variable (0,522) and compensation variable (0,113) with F value test (11,344). It is suggested to the company to maintain employee motivation in high level with improve competency employee with training and fix compensation that given by the company with review the value of compensation has been given, fix job promotion system so the employees keep in motivated to work wel